The convergence of traditionalism and populism in American politics from Bannon to Trump - Cheok, Adrian David (IGI Global, 2024)
"In the tumultuous landscape of contemporary American politics, the intricate dance between traditionalism, populism, and the influential alliance of Donald Trump and Steve Bannon poses a pressing challenge. As these ideologies shape the very fabric of society, scholars and academics grapple with the need for a comprehensive understanding of their historical roots, philosophical foundations, and consequential impact on issues such as immigration, globalization, and nationalism. The rise of the Trump-Bannon duo further intensifies the complexity, giving rise to controversies, challenges, and myriad unanswered questions about their lasting influence on American democracy. The Convergence of Traditionalism and Populism in American Politics: From Bannon to Trump address the gaps in understanding the relationship between traditionalism, populism, and the Trump-Bannon era. Offering a nuanced exploration, the author defines these ideologies and traces their roots, delves into their historical evolution, and examines their impact on American politics. The reader is guided through the ideological underpinnings of Trump and Bannon, gaining a profound insight into their political strategy and the challenges that defined their era."
"Premier reference source" -- from cover
Includes bibliographical references and index
Keywords: Trump, Donald / 1946-; Tradition (Philosophy); Populism / United States; Political culture / United States; Conservatism / United States; United States / Politics and government / 21st century